Terrorism in cyberspace: the next generation - Weimann, Gabriel (Woodrow Wilson Center Press, 2015)
Terrorism enters cyberspace -- Narrowcasting -- Lone wolves in cyberspace -- The e-marketing of terror -- Debates online -- Online fatwas -- Terror on social media -- Cyberterrorism -- Countermeasures : noise and the M.U.D. model -- The war of narratives -- Challenging civil liberties